2021
DOI: 10.31033/ijemr.11.3.24
|View full text |Cite
|
Sign up to set email alerts
|

Factors Implicated in Smartphone Usage Distressing Individual

Abstract: In today’s era usage of communication technology is increasing day by day whether it may be in the field of education or any other field. The dependency on these technological devices has been increased; it may be fruitful on one hand and problematic from some aspects on other side. People are not realizing the negative aspects of the usage but when they were asked they seemed to neglect the negative aspects as they are not concerned but some other day it will certainly affect them. The present study was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Empirically, some studies have shown that, in the context of telework, procrastinating behaviors influence the relationship between teleworking and well-being (e.g. Singh and Medhavi, 2021). For example, Arenas et al (2022) have shown that procrastination is a disadvantage for telecommuting as it creates conditions to impair performance and, as a result, well-being.…”
Section: The Moderating Role Of Procrastinationmentioning
confidence: 99%
“…Empirically, some studies have shown that, in the context of telework, procrastinating behaviors influence the relationship between teleworking and well-being (e.g. Singh and Medhavi, 2021). For example, Arenas et al (2022) have shown that procrastination is a disadvantage for telecommuting as it creates conditions to impair performance and, as a result, well-being.…”
Section: The Moderating Role Of Procrastinationmentioning
confidence: 99%